Implementation of a Community-Based Psychosocial Support Focal Point Response for Internally Displaced Persons in Myanmar During COVID-19 - Lee, Catherine; Schojan, Matthew; Myo, Ko; Doe, Gyaw Htet; San, Lanau Htu; Bass, Judith (Frontiers in Public Health, 2022)
Background In response to the COVID-19 pandemic, the Global Mental Health research group at Johns Hopkins School of Public Health worked with three local partner organizations in Myanmar to develop a psychosocial support (PSS) program that could be delivered by community-based focal points in internally displaced persons camps. This PSS program was designed to be delivered in communities with limited access to regional mental health services due to pandemic travel restrictions. The content of the PSS program was based on materials from an ongoing Common Elements Treatment Approach (CETA) mental health program; CETA counselors based in the three partner organizations were available to provide telephone-based CETA counseling. In April 2020, the partners organizations recruited and trained PSS focal points in 25 IDP camps to establish a multi-tiered system of MHPSS supports. Implementation The PSS program including psychoeducation handouts focused on stress and coping during COVID-19 and skills for cognitive restructuring (i.e., changing unhelpful thoughts) in simplified terms, audio recordings of the content of these handouts and referral opportunities for telephone-based services by CETA counselors located outside of the camps. PSS focal points distributed the handouts, had the recordings played via radio and loudspeaker, and were available to answer questions and provide access to a PSS program phones to connect with the CETA counselors. After 6 months of implementation, program monitoring logs were reviewed and a cross-sectional evaluation was conducted to assess the PSS program's reach, understanding, and perceived utility. Evaluation Forty-one focal points implemented the PSS program in 25 IDP camps in Kachin and northern Shan States. From May to September 2020, the focal points distributed handouts to 5,725 households and reported 679 visits by IDPs, including facilitating 332 calls to a CETA counselor. Data from the program evaluation (n = 793 participants) found high levels of handout readership and perceived utility of the information, and good comprehension of the content and application of skills. Discussion Findings suggest that provision of a multi-tiered MHPSS program, with PSS focal points providing direct information and linkages to further mental health services via telephone, was feasible despite the constraints of the pandemic. Utilizing camp-based focal points was acceptable and successful in delivering basic psychosocial supports to a broad population while serving as points of contact for individuals who wanted and needed telephone-based counseling services.